The Effectiveness of Restitution Rights for Child Victims of Domestic Violence in Indonesia under the CRC - Dehi, Amelia Putri; Towadi, Mellisa (Damhil Law Journal, 2025)
This study discusses the effectiveness of the implementation of restitution rights for children who are victims of domestic violence (DV) in Indonesia within the framework of the Convention on the Rights of the Child. Restitution, as a form of victim's rights recovery, is explicitly regulated in various national laws and regulations, yet its implementation still faces significant challenges on the ground. The research method used is normative juridical with a qualitative descriptive approach, through analysis of regulations, legal doctrines, and case studies of court rulings. The results of the study indicate that restitution plays a vital role in the physical, psychological, and social recovery of children who are victims of DV, while also emphasizing the responsibility of perpetrators for their actions. However, the implementation of restitution rights is still hindered by a lack of understanding among law enforcement officials, bureaucratic complexities, insufficient victim support, and obstacles faced by perpetrators in fulfilling their payment obligations. To address these issues, strengthening regulations, improving the capacity of officials, optimizing the role of child protection institutions, and fostering cross-sector collaboration are necessary to ensure that restitution rights become an integral part of the protection and recovery of child victims of DV in Indonesia.